Understanding the complexity of provincial-level elite sport policy change: The case of Shanghai municipality - Ma, Yang (Frontiers in Psychology, 2022)
The analysis of elite sport policy changes at the provincial level remains relatively uncharted territory despite the substantial contributions of provincial-level elite sport to national elite sport success. Data were gathered from semistructured face-to-face interviews and official and semiofficial documents. The key findings were that (1) Guangdong, as a provincial compatriot of Shanghai, has made tremendous efforts and obtained notable achievements in professional football and thus serves as a powerful stimulant for policy reform regarding elite sports in Shanghai; (2) the policy stream has been strengthened by knowledge-based (epistemic) communities at the Shanghai University of Sports that can examine cause and effect relationships and further propose specific policies; and (3) the general director of the Shanghai Administration of Sports plays a central role in advocating for policy proposals. The current research offers practical insights into strategies for reviewing policy trajectories to enhance policy design and implementation.